InterActive physiology digestive system - Fogel, Lauren; Dekel, Ziki; Mitchell, Susan
Interactive physiology offers detailed animations that bring complex physiological processes to life. Engaging tutorials, animations, quizzes and tests will help you understand some of the most difficult concepts in physiology. In this digestive system series, you can explore the orientation, motility, anatomy review, secretion, control of the digestive system and digestion and absorption.